Analisis Kesulitan Membaca Permulaan pada Siswa Kelas II SDN Kepadangan II - Fadilah, Rahma Maulidia Nur; Rozie, Fachrur (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Early reading difficulties are children's learning difficulties in reading in grades I and II. This study aims to determine the difficulties faced by grade II students when reading at the beginning, the factors causing difficulties learning to read, and the solutions provided by teachers to overcome them. The type of research used is descriptive qualitative research. The subjects in this study were grade II students of SDN Kepadangan II who had difficulty reading as many as four students and homeroom teachers. The technique used in determining the subject uses purposive sampling. Data collection techniques use observation, interviews, and documentation. The data analysis techniques used are reduction, presentation of data, and drawing conclusions. The result of this study was that there were 4 students who had difficulty reading beginning in recognizing letters A-Z, could not string words, were still hesitant in reading. The difficulty is caused by two factors, namely internal and external factors of students. Efforts that can be given by teachers are to create additional classes for reading, provide easier assignments according to their reading level, and by using flashcard media, and invite parents / guardians to pay more attention to reading learning activities at home.